Ariane de J. M. G. Le Clézio y la reescritura del mito del minotauro en el laberinto de una barriada alienante y fantasmal - Herrero Cecilia, Juan (Amaltea. Revista de Mitocrítica, 2009)
Following a methodology inspired by mythocritical theories by Brunel and Siganos, this essay focuses on the rewriting of the myth of the Minotaur and the labyrinth performed by J.M.G. Le Clézio in his narrative Ariane. Here the labyrinth adopts the form of an impoverished neighborhood in a contemporary city —a perfect backdrop to the tragic story of young Christine, who is chased by a gang of bikers acting by night “like a hoard of wild beasts.” This rewriting works implicitly, through allusion and analogy, by means of a series of images and associations interwoven in the narrator’s discourse. Particular emphasis has been placed in this essay on the concept of hybris, which the Greek related to disproportionate arrogance, to irrational impulse that breaks the limits of harmony.